Efficacy of keverprazan for duodenal ulcer: A phase II randomized, double‐blind, parallel‐controlled trial. Issue 11 (16th September 2022) - Tan, Nian‐di; Liu, Xiao‐wei; Liu, Cheng‐xia; Li, Sheng‐bao; Chen, Hong‐hui; Li, Xing; Wu, Hao; Liao, Ai‐Jun; Zhen, Yan‐bo; Shen, Peng‐zhen; Huo, Li‐juan; Liu, Hong‐ling; et al.
Abstract: Background and Aim: Considering the limitation of varying acid suppression of proton pump inhibitors, this study was aimed to assess the efficacy, safety, and dose–effect relationship of keverprazan, a novel potassium‐competitive acid blocker, in the treatment of duodenal ulcer (DU) compared with lansoprazole. Methods: A randomized, double‐blind, double‐dummy, multicenter, low‐dose, high‐dose, and positive‐drug parallel‐controlled study was conducted to verify the non‐inferiority of keverprazan (20 or 30 mg) to lansoprazole of 30 mg once daily for 4 to 6 weeks and dose–effect relationship of keverprazan in the treatment of patients with active DU confirmed by endoscopy. Results: Of the 180 subjects randomized, including 55 cases in the keverprazan_20 mg group, 61 cases in the keverprazan_30 mg group, and 64 cases in the lansoprazole_30 mg group, 168 subjects (93.33%) completed the study. The proportions of healed DU subjects in the keverprazan_20 mg, keverprazan_30 mg, and lansoprazole_30 mg groups were respectively 87.27%, 90.16%, and 79.69% at week 4 ( P  = 0.4595) and were respectively 96.36%, 98.36%, and 92.19% at week 6 ( P  = 0.2577). The incidence of adverse events in the keverprazan_20 mg group was lower than that in the lansoprazole_30 mg ( P  = 0.0285) and keverprazan_30 mg groups ( P  = 0.0398). Conclusions: Keverprazan was effective and non‐inferior to lansoprazole in healing DU. Based on the comparable efficacy and safety data, keverprazan of 20 mg once daily is recommended for the follow‐up study of acid‐related disorders. (Trial registration number: ChiCTR2100043455.)